New Approaches in Intelligent Control Techniques, Methodologies and Applications - Nakamatsu, Kazumi; Kountchev, Roumen; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume introduces new approaches in intelligent control area from both the viewpoints of theory and application. It consists of eleven contributions by prominent authors from all over the world and an introductory chapter. This volume is strongly connected to another volume entitled "New Approaches in Intelligent Image Analysis" (Eds. Roumen Kountchev and Kazumi Nakamatsu). The chapters of this volume are self-contained and include summary, conclusion and future works. Some of the chapters introduce specific case studies of various intelligent control systems and others focus on intelligent theory based control techniques with applications. A remarkable specificity of this volume is that three chapters are dealing with intelligent control based on paraconsistent logics.
New Approaches in Intelligent Control-Techniques, Methodologies and Applications- -- Design of Fuzzy Supervisor-based Adaptive Process Control Systems -- Intelligent Carpooling System. A Case Study for Bacău Metropolitan Area -- Naval Intelligent Authentication and Support through Randomization and Transformative Search -- Big Data Approach in an ICT Agriculture Application -- Intelligent Control Systems and Applications on Smart Grids -- Control Through Genetic Algorithms -- Knowledge-Based Intelligent Process Control -- Ciphering of Cloud Computing Environment Based New Intelligent Quantum Service -- Paraconsistent Logics and Applications -- Annotated Logics and Intelligent Control -- Paraconsistent Annotated Logic Program EVALPSN and its Application to Intelligent Control.
Keywords: Computational intelligence; Control engineering; Artificial intelligence; System theory; Control theory; Computational Intelligence; Control and Systems Theory; Artificial Intelligence; Systems Theory, Control